Wnt/β-Catenin signaling pathway in hepatocellular carcinoma: pathogenic role and therapeutic target - Zhao, Zekun; Cui, Tenglu; Wei, Fengxian; Zhou, Zhiming; Sun, Yuan; Gao, Chaofeng; Xu, Xiaodong; Zhang, Huihan (Frontiers in Oncology, 2024)
Hepatocellular carcinoma (HCC) is the most common primary malignant liver tumor and one of the leading causes of cancer-related deaths worldwide. The Wnt/β-Catenin signaling pathway is a highly conserved pathway involved in several biological processes, including the improper regulation that leads to the tumorigenesis and progression of cancer. New studies have found that abnormal activation of the Wnt/β-Catenin signaling pathway is a major cause of HCC tumorigenesis, progression, and resistance to therapy. New perspectives and approaches to treating HCC will arise from understanding this pathway. This article offers a thorough analysis of the Wnt/β-Catenin signaling pathway's function and its therapeutic implications in HCC.